"The Theme Of Conflict Between Individual And Society In Nissim Ezekiel's Plays Song Of Deprivation And Don't Call It Suicide" - Krishna, N. Anil (International Journal of Psychosocial Rehabilitation, 2020)
Nissim Ezekiel's plays are statements of human relationships. Like his poetry, his plays are also simple introspective, and analytical. All his five published plays--Nalini, Marriage Poem, Sleep Walkers, Song of Deprivation, and Don't Call It Suicide--examine the predicament of individuals in a world of complex realities H.H.Anniah Gowda remarks that Nissim Ezekiel has "an aptitude for writing plays composed of gusto and social comment." The treatment of social complexities is cent and dominant in Ezekiel's plays. If Nalini is a drama on the plight of the artist, Marriage Poem dramatizes hollow human relationships. Sleep Walkers ridiculed the mad imitation of Americanism, and Song of Deprivation speaks of freedom-loving lovers. Don't Call It Suicide portrays the situations confronted by the 'non-adjustment people of the society.